EKSPERIMEN PEMBUATAN MOTIF PADA KAIN DENGAN TEKNIK ECO PRINT DI SMP SWASTA AN-NIZAM MEDAN - Siti Hartinah Fitri; Sri Wiratma; Mesra Mesra (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
This research aims to find out how the process of making the pattern using eco print technique and to find out the aesthetic value eco print pattern on the work of first year students of Hasan Al-Banna Class at SMP Swasta An-Nizam Medan 2019/2020 Period. The aesthetic value of the eco print pattern reviewed based on the process of leaves laying, beating technique and steaming cloth. The research method used is descriptive qualitative method. The population in this research contained of four students. The sample used in this research contained of three students, using the Slovin formula, which is included the population size and error tolerance. The result of the research showed that overall the level of aesthetic quality pattern produced using eco print technique by the students first year of Hasan Al-Banna Class SMP Swasta An-Nizam Medan reviewed based on the process of leaves laying, beating technique and steaming cloth get good category results. On the value of leaves laying, beating technique and steaming cloth get good category results.Keywords: Experiment, Pattern, Eco Print Technique